Isbat Nikah terhadap Perkawinan di Bawah Umur Pasca Berlakunya Undang-Undang Nomor 16 Tahun 2019: Kajian Sosiologi Hukum atas Pengabulan Permohonan Pengesahan Nikah - Ahmad Nafari; Maya Sosilawati; Muhammad Aini (AHKAM, 2026)
The change in the minimum age of marriage through Law Number 16 of 2019 is a state effort to prevent child marriage and ensure the protection of children’s rights. However, the practice of marriages below the minimum age limit is still found in society and is subsequently submitted through marriage validation applications to the Religious Courts. This study aims to analyze the regulation of the minimum age of marriage in Indonesian positive law, identify the social factors that cause underage marriage, and examine the granting of marriage validation for such marriages from the perspective of sociology of law. This study uses a normative legal method with statutory, conceptual, and sociology of law approaches. Data were obtained through library research on relevant laws and regulations, books, and scholarly journals. The results of the study show that although underage marriage contradicts the provisions of positive law, judges in several cases still grant marriage validation applications by considering aspects of utility, protection for women and children, and the social realities of society. From the perspective of sociology of law, the granting of marriage validation reflects the adaptation of state law to the law living in society (living law). The conclusion of the study affirms that granting marriage validation for underage marriage is an effort to realize substantive justice without disregarding the objective of legal protection mandated by law. The implications of this study provide theoretical contributions to the development of the sociology of Islamic family law, as well as practical implications for the Religious Courts and policymakers in resolving the legal consequences of underage marriage.